Corporate Social Responsibility a Horizontal Approach for equitable Development in the construction of Rural sustainability - Murthy S, Venkatesh; Saravanan, Saravanan (Journal of Neonatal Surgery, 2025)
Rural development is an indispensable for developing countries. The role of public sector banks is not only accepting and lending money rather institutionalize the social activities and contribute to the rural development. Corporate social responsibility (CSR) is a form of international private business self-regulation which aims to contribute to societal goals of a philanthropic, activist, or charitable nature by engaging in or supporting volunteering or ethically-oriented practices. The present study is related to the rural development of state of Karnataka India through CSR activities by the public sector banks. In order to study this convenient sampling method is used for collecting sampling. It is descriptive in nature and primary data is collected form the rural respondents